Comparative research points to sub-Saharan African farmers’ willingness to pay for climate smart maize technologies and adoption dynamics and pathways - CGIAR Research Program on Maize (2021)
Climate change, including increased variability, challenges smallholder agriculture. It also affects the livelihoods of smallholder maize farmers. Enhanced adoption of climate smart technologies could help farmers. This very much depends on their willingness to pay for the technologies. Studies showed that farmers are willing to pay for climate smart technologies - and their growing improved, stress tolerant maize varieties has positively affected farmer livelihoods, thanks to increased on-farm yields (on average).